Starvation And Reactivation Of Partial Nitrifying Bacteria, Comparison Between Floccular And Granular Biomass - Tan, Teong Ee (2017)
In this study, nitrogen was removed from wastewater via partial nitrification using both floccular and granular biomass. The purpose of this study is to investigate the effect of starvation on nitrogen removing bacteria, changes of biomass in term of structure during starvation, and recovery ability of biomass. 2 Sequencing Batch Reactor (SBR) with working volume of 8L were operated to enrich floccular and granular biomass. Both floccular and granular biomass were cultivated using high strength synthetic wastewater in SBR operating under similar parameters except height/diameter (H/D) ratio and settling time. The height/diameter ratio of SBR used to cultivate granular biomass was 10 which was higher than floccular biomass (5). The settling period of granular biomass was stepwise decreased from 5 to 1 minute for the enhancement of granulation. The cultivated granular biomass has an average diameter of 2mm. The long term performance of floccular and granular biomass were consistent and the results showed that partial nitrification was achieved for both floccular and granular biomass. Comparison was made between floccular and granular biomass in starvation, reactivation and energy distribution. Starvation studies (carbon starvation and energy starvation) were carried out on both floccular and granular biomass. The starvation studies showed that carbon starvation (absence of carbon source, only energy source is provided) has lesser impacts in the activity of both floccular and granular biomass as compared to energy starvation (absence of energy source, only carbon source is provided). Granular biomass was found to be more resilient to the starvation as compared to floccular biomass due to slower rate of reduction in ammonium uptake. Furthermore, recovery study was carried out on both floccular and granular biomass after certain period of starvations (both carbon and energy starvations). The recovery study results showed that carbon starved biomass were able to recovery easily as compared to energy starved biomass. Carbon starved granular biomass was found to be more responsive to the recovery as compared to carbon starved floccular biomass. Prolonged recovery was required for energy starved biomass to reactivate. Energy starved granular biomass required shorter period to recover as compared to energy starved floccular biomass. Maintenance energy distribution study was carried out on both carbon starved floccular biomass and granular biomass. It was found out that granular biomass has higher maintenance energy distribution (89%) during normal condition as compared to floccular biomass (69%). The maintenance energy distribution of both floccular and granular biomass were not affected by the starvation (70%). However, it was believed that the disintegration of the granular structure after starvation induced similar behaviour to the floccular biomass, which was probably the reason behind the similar maintenance energy distribution after starvation.